Impact of the CYP2C19*17 Allele on Outcomes in Patients Receiving Genotype‐Guided Antiplatelet Therapy After Percutaneous Coronary Intervention. Issue 3 (2nd October 2020) - Lee, Craig R.; Thomas, Cameron D.; Beitelshees, Amber L.; Tuteja, Sony; Empey, Philip E.; Lee, James C.; Limdi, Nita A.; Duarte, Julio D.; Skaar, Todd C.; Chen, Yiqing; Cook, Kelsey J.; Coons, James C.; et al.
Abstract : Genotyping for CYP2C19 no function alleles to guide antiplatelet therapy after percutaneous coronary intervention (PCI) improves clinical outcomes. Although results for the increased function CYP2C19*17 allele are also reported, its clinical relevance in this setting remains unclear. A collaboration across nine sites examined antiplatelet therapy prescribing and clinical outcomes in 3, 342 patients after implementation of CYP2C19 ‐guided antiplatelet therapy. Risk of major atherothrombotic and bleeding events over 12 months after PCI were compared across cytochrome P450 2C19 isozyme (CYP2C19) metabolizer phenotype and antiplatelet therapy groups by proportional hazards regression. Clopidogrel was prescribed to a similar proportion of CYP2C19 normal (84.5%), rapid (82.9%), and ultrarapid metabolizers (80.6%) ( P  = 0.360). Clopidogrel‐treated normal metabolizers (20.4 events/100 patient‐years; adjusted hazard ratio (HR) 1.00, 95% confidence interval (CI), 0.75–1.33, P  = 0.993) and clopidogrel‐treated rapid or ultrarapid metabolizers (19.1 events/100 patient‐years; adjusted HR 0.95, 95% CI, 0.69–1.30, P  = 0.734) exhibited no difference in major atherothrombotic events compared with patients treated with prasugrel or ticagrelor (17.6 events/100 patient‐years). In contrast, clopidogrel‐treated intermediate and poor metabolizers exhibited significantly higher atherothrombotic event risk compared with prasugrel/ticagrelor‐treated patients (adjusted HR 1.56, 95% CI, 1.12–2.16, P  = 0.008). When comparing clopidogrel‐treated rapid or ultrarapid metabolizers to normal metabolizers, no difference in atherothrombotic (adjusted HR 0.97, 95% CI, 0.73–1.29, P  = 0.808) or bleeding events (adjusted HR 1.34, 95% CI, 0.83–2.17, P  = 0.224) were observed. In a real‐world setting of genotype‐guided antiplatelet therapy, the CYP2C19*17 allele did not significantly impact post‐PCI prescribing decisions or clinical outcomes. These results suggest the CYP2C19 *1/*17 and *17/*17 genotypes have limited clinical utility to guide antiplatelet therapy after PCI.